2022
DOI: 10.3389/fphar.2022.821691
|View full text |Cite
|
Sign up to set email alerts
|

Esketamine as an Adjuvant to Ciprofol or Propofol Sedation for Same-Day Bidirectional Endoscopy: Protocol for a Randomized, Double-Blind, Controlled Trial With Factorial Design

Abstract: Background: Same-day esophagogastroduodenoscopy and colonoscopy procedures under sedation have been increasingly performed. This study aims to assess the effects of esketamine combined with ciprofol (a novel anesthetic/sedative agent) or propofol on respiratory and hemodynamic adverse events in patients undergoing same-day bidirectional endoscopy.Methods: This is a prospective, randomized, double-blind, placebo-controlled, 2 × 2 factorial trial. A total of 180 adult patients scheduled for same-day bidirectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…We only recruited patients with ASA I-II and those who had a procedure time <30 min (eg, endobronchial inspection, bronchoscopic biopsy, and bronchoalveolar lavage). However, with the development of respiratory endoscopy technology, more complex endoscopic therapy is required under anesthesia, when there is no contraindication according to guidelines ( Wahidi et al, 2011 ; Strohleit et al, 2021 ; Long et al, 2022 ). A previous study reported that ciprofol produces similar levels of sedation compared with propofol in the intensive care unit setting to achieve required sedation times of 6–24 h ( Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We only recruited patients with ASA I-II and those who had a procedure time <30 min (eg, endobronchial inspection, bronchoscopic biopsy, and bronchoalveolar lavage). However, with the development of respiratory endoscopy technology, more complex endoscopic therapy is required under anesthesia, when there is no contraindication according to guidelines ( Wahidi et al, 2011 ; Strohleit et al, 2021 ; Long et al, 2022 ). A previous study reported that ciprofol produces similar levels of sedation compared with propofol in the intensive care unit setting to achieve required sedation times of 6–24 h ( Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, esketamine is increasingly replacing ketamine in clinical practice in China, especially in the application of short-duration and same-day surgeries [ 14 , 20 , 21 , 24 ]. Our research focused on determining the effective dose of esketamine to relieve propofol injection pain, and observing the clinical effect of low-dose esketamine in reduce pain from propofol injection.…”
Section: Discussionmentioning
confidence: 99%
“…Neither HR nor MAP was significantly decreased at 1 and 3 min after propofol induction. This may be due to the weaker sympathomimetic effect of esketamine at low doses, which counteract the inhibitory effect of propofol on the cardiovascular system [ 7 , 24 ]. Before and after propofol induction, SpO 2 was stable and no respiratory depression was observed, which may be related to the respiratory stimulatory effect of low-dose esketamine, which alleviated the inhibitory effect of propofol on respiration [ 7 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been adopted in some European countries for decades and has been used in Chinese hospitals in recent years. Besides treating depression, esketamine is applied for clinical sedation and analgesia associated with same-day bidirectional endoscopy ( Long et al, 2022 ), pediatric dental surgery ( Xin et al, 2021 ) and mechanical ventilation in ICU patients ( Song et al, 2022 ) When it is used for bronchoscopy, esketamine relaxes bronchiolar muscles and inhibits bronchial constriction ( Huang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%